Fear of Missing Out Culinary Tourism Students of UPI the Education of University Tourism Industry Study Program in Sumedang - Mukti, Widi Widya; Novarlia, Irena (UNIVERSITAS PAKUAN, 2025)
The purpose of this study is to analyze the behavior of fear of missing out in culinary tourism, related to anxiety or fear of missing out on something that is popular. As a result, Tourism Industry Study Program students tend to follow trends, buy goods that are not really needed, or do activities that are actually undesirable, so as not to feel left behind. The qualitative method with a phenomenological approach is used to focus on a deep understanding of the individual's subjective experience of a phenomenon. The data analysis technique used is Interpretative phenomenological analysis, which is a method that focuses on an in-depth exploration of how participants understand their personal experiences. Data collection techniques are carried out by observation, documentation, and in-depth interviews with informants. Data collected from key informants is more accurate and valid because it is in accordance with the phenomenon experienced directly. The results of the study show a change in fear of missing out behavior towards consumptive behavior, shown by the existence of social media promotions and consumption trends that encourage impulsive behavior and social anxiety. Thus, it is hoped that Tourism Industry Study Program students can face challenges in balancing modern social pressure and social media with values to prioritize life balance and build healthy relationships without relying on social media.